2012
DOI: 10.1128/jcm.00196-12
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Serological, and Virulence Characterization of Clinical and Oyster Vibrio parahaemolyticus Isolates

Abstract: In this study, 77 clinical and 67 oyster Vibrio parahaemolyticus isolates from North America were examined for biochemical profiles, serotype, and the presence of potential virulence factors (tdh, trh, and type III secretion system [T3SS] genes). All isolates were positive for oxidase, indole, and glucose fermentation, consistent with previous reports. The isolates represented 35 different serotypes, 9 of which were shared by clinical and oyster isolates. Serotypes associated with pandemic strains (O1:KUT, O1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
140
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(159 citation statements)
references
References 38 publications
(67 reference statements)
16
140
2
1
Order By: Relevance
“…Most of the strains belonging to serogroups O1 and O4 also were PCR positive for the hemolysin genes trh or tdh, or both (see Table S1 in the supplemental material). Jones et al (10) examined clinical isolates from across North America (July 2006 to November 2007) and oyster isolates collected across the United States in 2007 and found that the predominant serovars were the pandemic strain O1:KUT, followed by O4:K12, the most common serotype observed in human illnesses from the Pacific Northwest (8,10,11). Among the Canadian clinical isolates of V. parahaemolyticus isolated from 2000 to 2009, serovar O4:KII* (O4:K12 is a serotype of this group) was the most common, followed by the pandemic serovar O1:KUT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the strains belonging to serogroups O1 and O4 also were PCR positive for the hemolysin genes trh or tdh, or both (see Table S1 in the supplemental material). Jones et al (10) examined clinical isolates from across North America (July 2006 to November 2007) and oyster isolates collected across the United States in 2007 and found that the predominant serovars were the pandemic strain O1:KUT, followed by O4:K12, the most common serotype observed in human illnesses from the Pacific Northwest (8,10,11). Among the Canadian clinical isolates of V. parahaemolyticus isolated from 2000 to 2009, serovar O4:KII* (O4:K12 is a serotype of this group) was the most common, followed by the pandemic serovar O1:KUT.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we describe the use of pulsed-field gel electrophoresis (PFGE), multilocus sequence typing (MLST), ribotyping, serotyping, and virulence gene detection by PCR to study in detail the molecular epidemiology of V. parahaemolyticus strains isolated from Canadian patients (3,(9)(10)(11). A retrospective descriptive laboratory analysis of clinical V. parahaemolyticus isolates from across Canada (primarily British Columbia), which is available from the inventory of the National Microbiology Laboratory, Public Health Agency of Canada, was conducted.…”
mentioning
confidence: 99%
“…Other studies (19)(20)(21) have reported that the tdh gene is encoded and co-regulated with T3SS2a genes, and that the T3SS2b genes have been detected in trh-positive strains. Moreover, all isolates contain T3SS1 (19,20). Thus, the results of the assays for virulence genes in this study are consistent with those of previous reports.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the type III secretion system (T3SS) has been investigated as a potential indicator of virulence (15)(16)(17)(18). Most clinical strains contain two nonredundant T3SSs, T3SS1, and T3SS2 (19,20). T3SS2 has been further subdivided into T3SS2a and T3SS2b (21).…”
Section: Introductionmentioning
confidence: 99%
“…parahaemolyticus can be considered ubiquitous in the marine environment (Jones et al, 2012). In the present study we isolated a total of 203 isolates of V. parahaemolyticus from both water and molluscan shellfish samples.…”
Section: Antibiotic Sensitivity Of V Parahaemolyticus Strainsmentioning
confidence: 88%